Kajian Pengurusan Risiko Gangguan Bekalan Tenaga Elektrik dan Sistem Bekalan Kuasa Kecemasan di Hospital - Ismail, Muhammad Afiq; Omar, Roshartini; Kai Chen, Goh; Ta Wee, Seow (Research in Management of Technology and Business, 2021)
Risk management plays an important role in overcoming the problems faced by a building so that the operation of the building is not affected. Especially buildings such as public hospitals that provide health services to the community where disruptions to electricity supply and emergency power supply systems will affect the services provided. Therefore, the objective of this study is to examine effective risk management practices to address the problem of power outages and the use of emergency power supply systems in hospitals, to examine the challenges in implementing risk management in hospitals to address the risk of power outages and the use of emergency power supply systems. , and review the measures that need to be taken to reduce the risk of disruption of electrical power supply and emergency power supply systems in hospitals. Qualitative methods of interviews were used to help researchers conduct this study and questions in semi-structured form were used in the interview sessions conducted with several respondents from the hospital management and maintenance sections. The results obtained are three effective practices namely the guidelines of the Ministry of Health Malaysia (MOH), risk review and audit, and condition assessment report and Quality Assurance Program (QAP), the challenges identified are the use of Central Management Information System (CMIS) and Assets and Services Information System (ASIS) and time constraints from the engineering unit to perform regulatory work around the clock, while the steps taken are to review and review the maintenance work and increase cooperation between the hospital and the concession company. This study is expected to help enhance the capacity of management and improve existing practices in addressing the risk of power outages.